GaN HEMTs device modeling in high-power and high-frequency applications - Zhang, Juncheng (Nanyang Technological University, 2025)
Wide Band Gap semiconductor devices are widely used in the high-power and high-frequency applications. Power GaN HEMTs attract the attentions of many power device and circuit designers to achieve better chip performance. However, the investigation and improvement of GaN HEMTs are time-consuming and cost due to the complex device simulation models. In this paper, the physical models of the GaN HEMTs are investigated and analyzed to enhance the understanding of this kind of devices. The derived physical models are transformed into mathematical equations and compared with the simulation results on TCAD Silvaco. Apart from that, the veriﬁcation of the consistency between the simulation results and the fabricated device data is more essential. Therefore, an AlN/GaN HEMT with carbon doped device is fabricated to prove the consistency between physical models used in the simulation and the measurement data. In the simple structure test, the physical models ﬁt the simulation well, while the consistency begins to drop when the structure gets complex, which should be addressed by considering more accurate physical models in the future.